2013
DOI: 10.1186/1479-5868-10-113
|View full text |Cite
|
Sign up to set email alerts
|

Associations between sports participation, adiposity and obesity-related health behaviors in Australian adolescents

Abstract: BackgroundThe purpose of this study was to examine the relationship between organized sports participation, weight status, physical activity, screen time, and important food habits in a large nationally representative sample of Australian adolescents.MethodsNationally representative cross-sectional study of 12,188 adolescents from 238 secondary schools aged between 12 and 17 years (14.47 ± 1.25 y, 53% male, 23% overweight/obese). Participation in organized sports, compliance with national physical activity, sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
60
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 25 publications
11
60
2
5
Order By: Relevance
“…Although many studies reported an inverse association between youth sport participation and pediatric obesity, indicating those who actively participate in sports had fewer negative obesityrelated outcomes (see Table 3), data from six studies revealed no significant relationships between youth sport participation and pediatric obesity 25,35,36 or found only partial or weak relationships in sub-group comparisons. 46,48,55 Among studies that stated an existing association between youth sport participation and pediatric obesity, authors of three studies presented findings on doses of youth sport participation and responses of obesity.…”
Section: Relationship Between Youth Sport Participation and Pediatricmentioning
confidence: 89%
“…Although many studies reported an inverse association between youth sport participation and pediatric obesity, indicating those who actively participate in sports had fewer negative obesityrelated outcomes (see Table 3), data from six studies revealed no significant relationships between youth sport participation and pediatric obesity 25,35,36 or found only partial or weak relationships in sub-group comparisons. 46,48,55 Among studies that stated an existing association between youth sport participation and pediatric obesity, authors of three studies presented findings on doses of youth sport participation and responses of obesity.…”
Section: Relationship Between Youth Sport Participation and Pediatricmentioning
confidence: 89%
“…Für den Befund, dass Sportbeteiligung invers mit der Bildschirmmediennutzung assoziiert war, gibt es jedoch empirische Unterstützung. In einer australischen Studie ging bei 12-bis 17-jährigen Schülern eine stärkere Beteiligung an organisierten sportlichen Aktivitäten mit einer höheren Wahrscheinlichkeit einher, die nationalen Empfehlungen zur Bildschirmmediennutzung zu befolgen [43]. Auch in einer amerikanischen Studie war starke Internetnutzung mit geringerer Sportbeteiligung verbunden, moderate Internetnutzung jedoch mit einer höheren Sportbeteiligung [44].…”
Section: Introductionunclassified
“…This may help future intervention designs to be more inclusive and is consistent with the finding that there is no difference in participation in organised sports by weight status. 40 Similarly, sport participation has previously been shown to differ by SES, 19 while other research has found that SES and cultural background, but not BMI, predict dropout from sport. 41 There was also no clear association with sex, which is surprising, given that levels of physical activity and sports participation are lower in girls than boys.…”
Section: Weight-related and Sex-related Barriersmentioning
confidence: 95%